Case Report: A case of TAFRO syndrome with severe and prolonged thrombocytopenia: diagnostic pitfalls - Sato, Hironori; Kanno, Atsuhiro; Sato, Minato; Endo, Akari; Ito, Hiroki; Ohara, Takahiro; Shirota, Yuko; Sumitomo, Kazuhiro; Mori, Takefumi; Furukawa, Katsutoshi (Frontiers in Immunology, 2023)
Thrombocytopenia, anasarca, myelofibrosis, renal dysfunction, and organomegaly (TAFRO) syndrome is a rare condition with diverse clinical and pathological characteristics related to multi-organ damage. We report a case of TAFRO syndrome complicated by immune thrombocytopenia with prolonged fever and thrombocytopenia for several weeks. A 61-year-old man was transferred with sepsis caused by Enterococcus faecalis, and developed disseminated intravascular coagulation. Antibiotics treatment was initiated: however, low-grade fever and thrombocytopenia persisted despite the adequate antimicrobial treatment. Systemic edema, pleural effusion, and ascites had developed before hospitalization, and renal and liver function had deteriorated, resulting in progressive multi-organ damage. Prednisolone 40 mg/day was initiated based on the assumption of a condition in which excessive production of inflammatory cytokines would lead to systemic deterioration and fatal organ damage. Subsequently, the fever resolved, and renal function began to normalize. However, thrombocytopenia did not show much recovery trend after Helicobacter pylori eradication therapy and initiation of thrombopoietin receptor agonists. Bone marrow biopsy results showed normal bone marrow with no malignant findings. Alternatively, significant clinical signs met the diagnostic criteria for TAFRO syndrome, and a renal biopsy revealed thrombotic microangiopathy, which is also reasonable for renal involvement in TAFRO syndrome. The use of cyclosporine remarkably corrected the thrombocytopenia. We considered this a case of TAFRO syndrome that developed after sepsis with disseminated intravascular coagulation and performed the differential diagnosis of prolonged thrombocytopenia and excluded it. Although TAFRO syndrome is a unique disease concept, diagnostic criteria may consist of nonspecific elements such as generalized edema, thrombocytopenia, persistent fever, and elevated inflammatory response, and there are many differential conditions to exclude, requiring caution in diagnosing TAFRO syndrome.